2014
DOI: 10.3389/fnhum.2014.00344
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical substrates of action perception and understanding: an anatomic likelihood estimation meta-analysis of lesion-symptom mapping studies in brain injured patients

Abstract: Several neurophysiologic and neuroimaging studies suggested that motor and perceptual systems are tightly linked along a continuum rather than providing segregated mechanisms supporting different functions. Using correlational approaches, these studies demonstrated that action observation activates not only visual but also motor brain regions. On the other hand, brain stimulation and brain lesion evidence allows tackling the critical question of whether our action representations are necessary to perceive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 181 publications
9
105
0
1
Order By: Relevance
“…These regions fall within a broader functional network responsive to cognitive tasks devoid of meaningful socioemotional content (Van Overwalle, 2011;Jack et al, 2012). But they are more frequently regarded as forming a subset of the functional network thought to enable representation of the visual and somatomotor features of actions when they are perceived, performed, conceptualized, and verbally processed (Caspers et al, 2010;Kemmerer et al, 2012;Molenberghs et al, 2012;Pulvermuller, 2013;Watson et al, 2013;Rizzolatti et al, 2014;Urgesi et al, 2014;Kemmerer, 2015). This included a region of the left posterior MTG that has been associated with encoding the visual motion components of action concepts (Chen et al, 2008;Deen and McCarthy, 2010;Saygin et al, 2010;Wallentin et al, 2011;Humphreys et al, 2013;Watson et al, 2013).…”
Section: Brain Regions For Conceptualizing An Action At Different Loasmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions fall within a broader functional network responsive to cognitive tasks devoid of meaningful socioemotional content (Van Overwalle, 2011;Jack et al, 2012). But they are more frequently regarded as forming a subset of the functional network thought to enable representation of the visual and somatomotor features of actions when they are perceived, performed, conceptualized, and verbally processed (Caspers et al, 2010;Kemmerer et al, 2012;Molenberghs et al, 2012;Pulvermuller, 2013;Watson et al, 2013;Rizzolatti et al, 2014;Urgesi et al, 2014;Kemmerer, 2015). This included a region of the left posterior MTG that has been associated with encoding the visual motion components of action concepts (Chen et al, 2008;Deen and McCarthy, 2010;Saygin et al, 2010;Wallentin et al, 2011;Humphreys et al, 2013;Watson et al, 2013).…”
Section: Brain Regions For Conceptualizing An Action At Different Loasmentioning
confidence: 99%
“…Specifically, the Why > How contrast reliably reveals activation in the dorsomedial and ventromedial prefrontal cortex (PFC), the anterior superior temporal sulcus (STS), the temporoparietal junction (TPJ) and the posterior cingulate cortex (PCC)-regions that have been independently implicated in representing and reasoning about the mental states that typically drive actions, such as beliefs, desires and intentions (Gallagher and Frith, 2003;Saxe, 2006;Carrington and Bailey, 2009;Van Overwalle and Baetens, 2009;Mar, 2011;Denny et al, 2012;Schurz et al, 2014). Conversely, the How > Why contrast reliably activates the dorsal and ventral premotor cortex (PMC), posterior middle temporal gyrus (MTG), rostral inferior parietal lobule (IPL) and dorsal precuneusregions that have been independently implicated in representing the visual motion patterns and somatomotor features of actions when perceived and performed (Caspers et al, 2010;Molenberghs et al, 2012;Rizzolatti et al, 2014), conceptualized (Kemmerer et al, 2012;Watson et al, 2013;Urgesi et al, 2014), and verbally processed (Kemmerer et al, 2012;Pulvermuller, 2013;Kemmerer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Data from both neuropsychological lesion studies (see Urgesi, Candidi, & Avenanti, 2014, for a recent meta--analysis) and 'virtual lesion' brain stimulation studies (summarised in indicate that mirror neuron brain areas -in particular, premotor cortex -are required for tasks involving the perception of others' actions. However, few if any of these studies use tasks involving intention understanding.…”
Section: The Role Of Mirror Neurons In Action Perception and Intentiomentioning
confidence: 99%
“…The preliminary 3-way ANOVA (gender*size*implied motion) on the VAS scores for the liking judgment at baseline showed that participants preferred slimmer rather than fat models (63.22 ± 2.14 mm vs. 30.30 ± 1.52 mm; F(1, 35) while same-gender models were preferred over opposite-gender models when they were depicted in the slim figures (65.25 ± 2.74 mm vs. 61.19 ± 3.1 mm; p = 0.033), they were liked less than opposite-gender models when they were depicted in the round figures (27.23 ± 1.9 mm vs. 33.37 ± 2.31 mm; p = 0.002). Thus, the way in which the perceived body weight affected aesthetic appreciation was different for same and different gender models.…”
Section: Resultsmentioning
confidence: 96%
“…In fact, rTMS over PMC impairs visual discrimination of static and dynamic displays of moving body parts (Pobric & Hamilton, 2006), suggesting that motor representations are necessary for visual discrimination of others' actions (Avevanti et al, 2013;Urgesi et al, 2014). Furthermore, activity of dPMc while watching dance is influenced by the motor expertise of the observer (Calvo-Merino et al, 2005 and is associated with the greater aesthetic appreciation of larger displacements of the dancer's limbs (Calvo-Merino et al, 2008).…”
Section: Discussionmentioning
confidence: 99%